Analgesic Activity of Acyl-Salicylic Acid Derivatives And In Silico Docking Study For Their Potency As Cyclooxygenase-2 Inhibitors - Nuzul Wahyuning Diyah; Anindi Lupita Nasyanska; Bambang Tri Purwanto; Siswandono Siswandono (Universitas Airlangga, 2020)
A series of acyl salicylic acid derivatives were screened to investigate their analgesic activities and their potency as cyclooxygenase-2 (COX-2) inhibitors. Fourteen compounds (BS1–14) were assayed by acetic acid induced writhing test. Their ability for interaction with COX-2 was studied through a docking simulation at the COX-2 active site (PDB. 5IKQ). The results of the analgesic activity test gave 3 compounds that produce ED50< 0.39 mmol/kg body weight, lower than aspirin as a positive control. The compounds BS3 and BS4 showed excellent analgesic activity and the tert-butyl substituted molecule BS3 (O-(4-tert-butylbenzoyl)-salicylic acid analog) showed the highest analgesic activity with ED50 of 0.26 mmol/kg. Based on in silico molecular docking, it is known that almost all of the tested ligands (12 compounds) showed a higher binding affinity for COX-2 than meclofenamic acid which is a COX-2 inhibitory NSAID. The results of in vivo analgesic activity were justified with the outcome of in silico investigation. Molecular docking of acyl-salicylates confirmed in vivo experiments and it was found that BS3 was the most active compound as an analgesic agent and the most potent as a COX-2 inhibitor among the evaluated compounds.a